Treatise on biblical rhetoric - Meynet, Roland, 1939- (International Studies in the History of Rhetoric, 2012)
The specific laws of composition of biblical texts, which were first discovered from the mid-eighteenth century, are becoming increasingly well-known. This Treaty represents the sum of Biblical and Semitic rhetoric, in an abridged translation of the French original. The first chapter traces the history of the discovery of biblical rhetoric, the last chapter opens future prospects. The main text of the book is organized into three sections covering the three major fields of research: 1. Composition: The Levels of Composition, The Figures of Composition, Rewriting. 2. Context: Intratext, Intertext, The Center of concentric constructions. 3. Interpretation: Editing and translating, Composition and Interpretation, Intertext and Interpretation, The gift of interpretation. Numerous examples illustrate this methodical and rigorous exposition.